Research on Joint Distribution Route Optimization of Cold-chain Logistics for Fresh Agricultural Products. Issue 4 (October 2020) - Yang, Xuewen; Zhang, Zhiguo; Wu, You
Abstract: In order to meet the development speed of cold-chain logistics, it is essential to enhance the efficiency of cold chain logistics, reduce the damage of fresh agricultural products, as well as guarantee the final transportation effect of all kinds of agricultural products. In view of the application of the Internet of things and the transportation principle of low temperature logistics, then the pattern of joint distribution is adopted, and the fixed cost, the transportation cost of distribution vehicles, the damage cost of fresh agricultural products and the operation cost of IOT are considered comprehensively. Under the basic setting of sufficient assumptions, the total cost to be lowest is taken as the objective function to construct a mathematical model to enhance the actual operation of cold-chain logistics in a scientific way.